A study of torture victims at the centre for the study of violence and reconciliation (CSVR), using the harvard trauma questionnaire (HTQ) as an assessment tool - Jayrajh, Preethi (My University, 2019)
Refugees and Asylum Seekers often flee their countries of origin fearing persecution. Many of these people have faced trauma including torture. Torture is associated with psychiatric sequalae, commonly Post Traumatic Stress Disorder (PTSD) and Major Depressive Disorder (MDD). This study looks at the psychiatric outcomes of torture and/or trauma victims, their demographic profile and whether differences in outcomes exist between exposure to physical trauma and other forms of trauma. Objectives To assess the psychiatric outcomes of attendees at the Centre for the Study of Violence and Reconciliation (CSVR), the majority of whom are refugees and asylum seekers. To specifically assess for symptoms of Post Traumatic Stress Disorder (PTSD) and Major Depressive Disorder (MDD). To assess the demographic profiles of the patients who presented at this clinic and their associations with PTSD and MDD symptoms. To determine if specific types of torture determine different outcomes. Methods A retrospective record review was conducted at the CSVR of patients who presented from the 01 January 2014 to 03 July 2017. A total of 227 patients were included in the study. The CSVR assessment tool was used. This includes section IV of the Havard Trauma Questionnaire and the Hospital Anxiety and Depression Scale. Results This study found that being widowed, unemployed or originating from Ethiopia, Somalia or The Democratic Republic of Congo (DRC) significantly predicted Major Depressive Disorder. No significant association was made with PTSD. Of the sample, 164 (72, 2%) screened positive for PTSD and 142 (62.5%) screened positive for Depression. Despite the majority screening positive for psychopathology, only 21.2% of the patients were referred to a psychiatrist for further intervention. Only 16.7% of the sample were placed on pharmacotherapy. Sexual Abuse/Rape significantly predicted MDD. There was a trend towards developing MDD after witnessing torture.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry. October 2019